2013
DOI: 10.1177/1535370212473696
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin protects against deleterious cardiovascular consequences induced by chronic intermittent hypoxia

Abstract: Chronic intermittent hypoxia (IH), a major component of obstructive sleep apnea (OSA), contributes to the high risk of cardiovascular morbidity. We have previously demonstrated that IH-induced oxidative stress is involved in the hypertension and in the hypersensitivity to myocardial infarction. However, the mechanisms underlying these cardiovascular alterations are still unclear, as well as the role of potential protective treatment. Atorvastatin has pleiotropic actions, including increasing nitric oxide (NO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
6
31
0
Order By: Relevance
“…Our data are consistent with the literature, which reports the following: (1) an independent association between OSA and hypertension in humans34 and (2) a determinant role of chronic IH in inducing elevation of arterial and blood pressure in healthy humans and animals exposed to IH 35, 36, 37. We further demonstrated that, in addition to the elevation of arterial blood pressure, IH also induces an arterial inflammatory remodeling with subsequent stiffening.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data are consistent with the literature, which reports the following: (1) an independent association between OSA and hypertension in humans34 and (2) a determinant role of chronic IH in inducing elevation of arterial and blood pressure in healthy humans and animals exposed to IH 35, 36, 37. We further demonstrated that, in addition to the elevation of arterial blood pressure, IH also induces an arterial inflammatory remodeling with subsequent stiffening.…”
Section: Discussionsupporting
confidence: 92%
“…These data are in accordance with clinical observations, demonstrating a significant increase in the carotid artery intima‐media thickness in patients with OSA that correlates to the severity of nocturnal hypoxemia 38, 39, 41. In rodent models, exposure to at least 14 days of IH resulted in enlarged intima‐media thickness and/or disruption of the elastic network 10, 11, 12, 37, 42, 43. In addition to structural remodeling, arterial stiffness and hypertension are also under the control of endothelial‐derived mediators, such as NO,40 and reduced NO bioavailability contributes to endothelial dysfunction, which represents a hallmark of hypertension and arterial stiffening.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Buchner et al (9) demonstrated that OSA patients exhibit an increase in infarct size after an ischemic event compared with patients without OSA. Several animal studies have confirmed these clinical observations and demonstrated that IH induces an elevation of mean arterial blood pressure (BP) and increases myocardial infarct size after ischemia-reperfusion protocols (6,35,54,57,62).…”
mentioning
confidence: 53%
“…21) and an increase in arterial BP (6,35,57,62). As ER stress inhibitors have been shown to prevent both ANG II-induced systemic hypertension (37) and hypoxiainduced pulmonary arterial hypertension (42) in mice, our data suggest that prolonged ER stress induced by IH could contribute to the IH-induced elevation of arterial BP.…”
Section: Ih-induced Increase In Bp and Infarct Size: Potential Role Omentioning
confidence: 66%
“…The other novel biomarkers discovered, having a role in developing hypertension in OSA include Nesfatin-1, Fibrinogen, and YKL-40 (also referred to as human cartilage glycoprotein) 42 . A study successfully demonstrated the protective effects of atorvastatin against deleterious effects of inflammation on cardiovascular consequences induced by chronic intermittent hypoxia using murine model 46 .…”
mentioning
confidence: 99%